Oral Health Knowledge, Attitudes, and Practices of Individuals with Diabetes Mellitus in the Sultanate of Oman - Noora Al Shihi; Abdulhakeem Al Rawahi; Raya Al Jahdhami; Rayyan Al Riyami; Abdulaziz Al Murazza; Noor Al Busaidi; Fatma Al Riyami; Suad Al Salti (Dubai Diabetes and Endocrinology Journal)
Introduction: Diabetes mellitus is a chronic disease with an increasing global prevalence. The condition has several oral health implications, with oral health in turn affecting diabetes control. People with diabetes are at higher risk of oral health problems, including periodontal disease, dental caries, and candidiasis; in particular, there appears to be a two-way relationship between periodontitis and blood glucose control. While previous research has indicated that diabetics have poor awareness of oral health, there is a gap in the literature from the Sultanate of Oman. This study aimed to determine oral health knowledge, attitudes, and practices among Omani diabetics. Materials and Methods: A cross-sectional study was conducted using a convenience sample of 400 adult Omani diabetics who attended the outpatient clinic of the National Diabetes and Endocrine Center, Oman, in the period between May 2019 and May 2020. A self-administered, Arabic language questionnaire to assess oral health knowledge, attitudes, and practices was developed and validated. Mean scores were calculated to determine overall levels of oral health knowledge, attitudes, and practice. Ethical approval was obtained from the Center of Studies and Research of the national Ministry of Health. Results: A total of 136 (34.0%) male and 264 (66.0%) female Omani adult diabetics participated in the study. The majority of participants (76.8%) demonstrated poor knowledge of oral health, especially with regards to complications like gingivitis (32.4%), dental caries (27.3%), halitosis (27.1%), and gingival abscesses (21.5%). Moreover, most (76.6%) were unaware that oral diseases affected glycated hemoglobin levels. In terms of practices, more than half (54.74.8%) routinely brushed their teeth twice a day. However, only 14.6% and 12.6% regularly flossed and used mouthwash, respectively. With regards to attitudes, 0.5%, 23.8%, and 75.8% of the participants demonstrated poor, moderate, and good attitudes toward oral health, respectively. Smokers more frequently demonstrated poor attitudes compared to nonsmokers (6.3% vs. 1.6%). Conclusion: Omani adults with diabetes mellitus demonstrated poor to moderate levels of oral health knowledge. Various studies conducted elsewhere around the world have similarly shown that diabetics have limited knowledge and awareness of oral health. Oral self-care behaviors are imperative to minimize the risk of oral health complications associated with diabetes. Previous researchers have shown that education is an effective method of reducing the incidence and burden of diabetes-related oral health complications. Thus, additional multidisciplinary initiatives are needed to raise awareness of good oral hygiene practices among diabetics in Oman.